ANTAGONIST VERSUS AGONIST MUSCLE NEUROMUSCULAR ELECTRICAL STIMULATION ON SPASTICITY IN STROKE PATIENTS (International Journal of Physiotherapy, 2017)
Background: Spasticity is the common problem encountered in the treatment of hemiplegic patients. Various treatment techniques have been developed to reduce spasticity, neuromuscular electrical stimulation is one of them. Several studies have proved that stimulation of either spastic muscle or stimulation of antagonist muscle to spastic muscle results in a reduction of spasticity. However, there is no literature available on a comparative study to suggest which method is more effective in spasticity reduction. Hence this study was undertaken to find out the efficacy of each technique and to compare the two techniques of Neuromuscular electrical stimulation to determine the most effective technique.Methods: In this study with pre and post-experimental design 30 post-stroke patients were selected and they were randomly assigned into two groups. Group A received anatagonist (triceps) muscle Neuromuscular electrical stimulation and Group B received agonist (biceps brachii) muscle Neuromuscular electrical stimulation for 2 weeks, one session per day for a duration of 30 minutes. Outcome measures were recorded using modified Ashworth scale and deep tendon reflex grading scale.Results: Statistical analysis was carried out by using Wilcoxon signed rank sum test and Mann-Whitney U test at 0.05 level of significance. There was a significant recovery after the treatment based on the Modified Ashworth Scale and deep tendon reflex grading scale scores before and after the intervention within the groups and between the groups with p-value< 0.001. The group receiving the antagonist muscle neuromuscular electrical stimulation showed better recovery with a mean difference of 1.8 and 1.2 on Modified Ashworth Scale and reflex grading scale respectively.Conclusion: The study concluded that both the techniques resulted in reduction of spasticity and on comparison it was found that antagonist muscle (triceps) Neuromuscular electrical stimulation reduced spasticity more effectively than the agonist muscleNeuromuscular electrical stimulation